Tunable Fermi acceleration in a nondissipative driven magnetic billiard - Castaldi, B. [UNESP]; Egydio de Carvalho, R. [UNESP]; Vieira Abud, C.; Mijolaro, A. P. (Amer Physical Soc, 2014)
We study the effect of a constant magnetic field on the dynamics of a system that may present Fermi acceleration (FA). The model in consideration is the nondissipative annular billiard with breathing boundaries. There is a field threshold, from which the mechanism of FA can be deactivated. The presence of the magnetic field curves the particle trajectories and for some combinations of the parameters FA is totally, and nontrivially, suppressed without considering any kind of dissipation.